Institutions of Inclusion and Exclusion - Vrooman, J. Cok (2020)
This thematic issue aims to shed light on the connections between institutions (and related forms of organisation) and social inclusion and exclusion. In this editorial we briefly introduce the concepts, summarise the various articles and provide some general conclusions.